THE USE OF VISUAL MEDIA TO IMPROVE THE STUDENT’S MOTIVATION AND ACADEMIC ACHIEVEMENT IN LEARNING ENGLISH AT THE SECOND YEAR OF SMK MUHAMMADIYAH 3 GEMOLONG IN 2009 / 2010 ACADEMIC YEAR - PRAMONO , SIGIT (2010)
This study is aimed to know the students’ motivation during English teaching learning process using visual media and to describe the achievement of them in the test result. The result of this study hopefully will give contribution in learning English. In this research, visual media are used to improve students’ motivation and achievement in learning English. This research was carried out at SMK Muhammadiyah 3 Gemolong, especially in class 2 Ak1 that consists of 34 students. To collect the required data, the writer did observation to know the students’ motivation and gave test to know academic achievement of students. There were two cycles in this action research in which each cycle used pre-test and post-test. He analyzed the data by comparing the result of pre-test and post-test. The results of pre-test and post-test were used to know the score of the vocabulary mastery. The mean of the achievement after the teacher did the action was 77.94 that belong to good category. While, before the teacher did the action, the mean of the students achievement was 60 that belongs to poor. Based on the research finding, it can be concluded that (1) visual media can increase the students’ motivation in learning English. All of the characteristics of motivated students were achieved in the second cycle. (2) Visual media can increase the students’ academic achievement in learning English. The students’ score was getting better in each cycle. It indicated that the teaching-learning process was successful, both the researcher and the students gained the objectives.